2021
DOI: 10.1109/access.2021.3073315
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation of Influencing Factors Regarding Offshore Outsourcing Decision of Application Maintenance

Abstract: Global Software Development (GSD) has been an emerging trend in the development of software globally, for the last two decades. Information Technology (IT) outsourcing includes application development, application maintenance, infrastructure management and business process outsourcing. Software maintenance aims to keep the IT system operational and to fulfill the client requirements. The maintenance is considered the longest phase of software life cycle that consumes about 60-70% of the total software budget. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 57 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…The influencing factors were further evaluated in the outsourcing industry by performing an empirical study [1] that ranked 10 factors as critical success factors. In the current study, a MCDM model is developed based on the influencing factors identified in [2,3], and which were further validated and reported in [1]. Literature review showed that previous studies [5,24,28,30,38,39] also adopted the same method.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The influencing factors were further evaluated in the outsourcing industry by performing an empirical study [1] that ranked 10 factors as critical success factors. In the current study, a MCDM model is developed based on the influencing factors identified in [2,3], and which were further validated and reported in [1]. Literature review showed that previous studies [5,24,28,30,38,39] also adopted the same method.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…This brings down the cost of software development by utilizing the employees with high skill sets and a wide pool of global resources as well as accessing cheaper resources and global talent. In addition, GSD provides opportunities, such as the development of software by following the sun, software development round the clock, access to qualified developers and engineers, access to online available resources, and obtaining economic as well as business growth [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations